Analysis of the application of venom from tropical spider families for different pharmacological therapies - Córdoba-Fernández, Eunice (2025)
Tropical spider venom has gained increasing attention in the medical field due to its richness in toxins with therapeutic potential. These substances, which have independently evolved in multiple arthropod lineages, exhibit promising pharmacological properties for the treatment of erectile dysfunction, autoimmune diseases, neurodegenerative disorders, cancer, and chronic pain. The objective of this study was to compile and analyze scientific evidence on the main experimental therapies developed from tropical spider venom. To this end, an extensive literature review was conducted focusing on compounds isolated from representative species such as Phoneutria nigriventer, Pardosa astrigera, Psalmopoeus cambridgei, and Acanthoscurria gomesiana. Among the most relevant findings are the use of the toxin PnTx2-6 from P. nigriventer, associated with erection mechanisms; the antimicrobial and anti-inflammatory peptides from wolf spiders (Lycosidae); the neuroprotective and analgesic action of psalmotoxin-1; and the anticancer potential of gomesin extracted from tarantula hemolymph. Overall, the results suggest that tropical spider venom represents a valuable source of bioactive compounds with medical applications. However, its research requires a regulated and sustainable approach that respects biodiversity and existing regulations.